Analisis Kualitatif Aksesibilitas Pengguna Kursi Roda di Hotel Pan Pacific Orchard - Angelia Stephanie; Gunawan Tanuwidjaja; Kenny David Ariyanto; Nathanael Nyoto (Petra Christian University, 2025)
Accessibility for wheelchair users is a crucial aspect of inclusive hospitality facility design, especially in countries with an aging population such as Singapore. With 13.3% of the population aged over 50 in 2024 and a projected 28.6% by 2030, the need for accessible spaces is becoming increasingly urgent. This study employed a content analysis method with a descriptive approach, in which the architectural floor plan of the Pan Pacific Orchard Hotel was redrawn and overlaid against the accessibility standards set by the Building and Construction Authority. The evaluation focused on five key elements: safety, visual focal points, corridors, cores, and user well-being. The findings indicate that the hotel not only meets technical accessibility requirements but also successfully integrates aesthetic elements with safety functions. Reflectively, this study highlights how the application of universal design can contribute to the creation of inclusive, meaningful, and adaptive spatial experiences for users with limited mobility. As such, the hotel serves as a model of design that promotes sustainability and competitiveness in the global hospitality sector.